Reforming Education:A Review of the Contributions of Benjamin Levin, Ph.D. - Laura Elizabeth Reimer (Canadian Society for Studies in Education, 2009)
One of Canada's beacons in the theory and practice of educational reform is Dr. Benjamin Levin. Dr. Levin's steadfast commitment to improving education is rooted in a unique career that has alternated between academia as a scholar and an intimate knowledge of the workings of government as a senior provincial public servant. His publications are accessible to those within educational scholarship and within the political environments of public and educational administration. This paper explores and celebrates the continuing career and contributions of Dr. Levin.